Peranan Pemimpin Lokal dalam Meningkatkan Kemampuan Kelompok (Kasus Kelompok Tani di Desa Pulo Kencana Kecamatan Pontang Kabupaten Serang) - Helda Ibrahim; Majdah Zain; Tanzil Ibrahim (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
Local leaders have a role as opinion leaders and development agencies in supporting the realization of a dynamic group in improving the ability of groups related to communication, motivation, to facilitating and social contacts, knowledge of groups and foster group experience. Rural communities still face problems, especially individuals that have not been able to develop itself in enhancing the ability of the group through the role of local leaders. The purpose of this study is to identify the role of local leaders in improving the ability of a group. This research was conducted in the village of Pulo Kencana, helter subdistrict, Serang regency. The number of respondents was 45 respondents with tree of farmer groups. The results showed that the role of local leaders in improving the ability of the group is high. This is due to the behavior on the actions of the leaders in facilitating the communication, increasing the motivation of group members and facilitating the group.Key words: local leaders, leaders role, groups ability